Relationship between vertical stiffness and soft-tissue injuries in professional Australian football. Issue 21 (2nd November 2019) - Sporri, Daniel; Pine, Matthew J.; Cameron, Matthew L.; Spurrs, Robert W.; Sheehan, William B.; Bower, Robert G.; Watsford, Mark L.
ABSTRACT: Soft-tissue injuries are common in Australian football. Recently, literature has identified non-modifiable and modifiable risk factors, including vertical stiffness (Kvert ). However, limitations regarding measurement frequency and duration exist; thus, further information is required about the role of Kvert as a modifiable risk factor for injury. This study examined the seasonal variation in Kvert and its relationship to soft-tissue injuries in professional Australian football. The mean Kvert and bilateral asymmetry were assessed and compared between injured and non-injured players. For the seasonal analysis, 56 players were tested across two seasons with no variation in bilateral asymmetry evident ( p = 0.33). While there were generally no changes in Kvert, the value from the end of the second pre-season revealed 5% lower values than the mean of two seasons ( p = 0.02). Considering the injury analysis, 21 lower-body soft-tissue injuries were recorded from 18 participants. No differences were recorded for mean Kvert between the injured and non-injured groups ( p = 0.16–0.76). When assessing Kvert asymmetry, the injured group displayed a 4.5% higher value than the non-injured group at the end of the pre-season test ( p = 0.03) but not at other time-points ( p = 0.16–0.99). Higher Kvert bilateral asymmetry measures after the pre-season appear to be related to lower-body soft-tissue injury in professional Australian footballers. Medical and conditioning staff should consider this measure when trying to mitigate the onset of injury or identify at-risk players.